EVALUASI PROGRAM KELOMPOK INFORMASI MASYARAKAT (KIM) PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN MERAUKE - Sumiasih; Aenal Fuad Adam; Nur Jalal; Syahruddin (PAPSEL Research and Consulting, 2025)
The Community Information Group (KIM) program is a strategic initiative by the Department of Communication and Information Technology of Merauke Regency to encourage active community participation in managing information and communication. This study aims to evaluate the effectiveness of the KIM program's implementation, covering aspects of planning, execution, and its impact on the community. The research method employed is a qualitative approach, with data collection techniques including interviews, observations, and document studies. The evaluation results indicate that the KIM program has positively contributed to improving community information literacy, particularly in rural areas. However, several challenges were identified, such as limited human resources, uneven technological infrastructure, and low community participation in certain activities. Therefore, strategic measures are needed, including enhancing the capacity of KIM members, expanding access to information technology, and optimizing synergy between local government, local communities, and other stakeholders. This study is expected to serve as a reference for developing a more effective and sustainable KIM program in the future.